Anaphylactic shock due to Aprokam application to the anterior chamber during cataract surgery – case report - Kędziora, Waldemar; Żarnowski, Tomasz (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Intracameral application of Aprokam (cefuroxime) during cataract surgery is documented to significantly reduce the incidence of endophthalmitis. It is very important to consider its very rare but potentially very dangerous complication, that is anaphylactic reaction of varying severity in patients at risk of such allergy. It is necessary to take a detailed history and check all relevant medical records concerning previous treatment to avoid this complication.